Nano-titania modified cupric-based metal–organic frameworks for the on-line pass-through cleanup of phenothiazine drugs and metabolites in human plasma. (1st July 2022) - Gan, Lu; Zhao, Yong-Gang; Yu, Cun; Ye, Ming-Li; Lu, Yin; Xiao, Shan-Mei; Zhang, Yun
Abstract : SEM (A) and TEM (B) images of NTMCu-MOFs. Abstract : We report nano-titania modified cupric-based metal–organic frameworks (NTMCu-MOFs) by a simple and low-cost solvothermal method. The excellent properties of the NTMCu-MOFs are characterized by transmission electron microscopy (TEM) and scanning electron microscopy (SEM). The NTMCu-MOFs have been evaluated in an on-line pass-through cleanup procedure as a sorbent prior to the analysis of phenothiazine drugs and metabolites, i.e., chlorpromazine (CPZ), promethazine (PMZ), chlorpromazine sulphoxide (CPZSO) and promethazine sulfoxide (PMZSO), in human plasma by liquid chromatography–tandem quadrupole mass spectrometry (LC-MS/MS). Endogenous matrices in human plasma samples were effectively removed by the NTMCu-MOF based on-line pass-through cleanup procedure and ion suppression effects were dramatically reduced. Under optimum conditions, satisfactory recoveries were found to be in the range of 85.6%–108%. Acceptable trueness and precision of the proposed method were also obtained, with relative errors (REs) less than 15% and within- and between-run RSDs less than 8.0%. The limits of detection (LODs) of phenothiazine drugs and metabolites were in the range of 0.012–0.024 μg L −1 . The proposed method has been used for the determination of phenothiazine drugs and metabolites in the plasma samples obtained from nine schizophrenic patients undergoing chlorpromazine therapy. The results demonstrated the applicability of the proposed NTMCu-MOF on-line pass-through cleanup procedure coupled with the LC-MS/MS method to clinical studies.